Key technologies and application scenario of DC/OS - Jiheng ZHANG; Dazhong LI; Chengyu ZHANG; Jinwu WEI (Dianxin kexue)
Firstly, critical technologies in data center operating system（DC/OS）, including Mesos, Yarn, Kubernetes and Docker were presented. Based on the current situations and problems that both domestic and foreign telecom operators faced, a simple resolution was proposed and technical realization as well as the selection of techniques were discussed. At last, several cases of DC/OS application for telecom operator were introduced.